2008
DOI: 10.1055/s-2008-1027208
|View full text |Cite
|
Sign up to set email alerts
|

„Basketball Foot” - Prognose nach medialer subtalarer Luxation

Abstract: Subtalar dislocation is considered a severe injury but occurs rarely and studies generally refer to relatively small patient collectives. We investigated the functional outcome in 22 cases to determine the long-term prognosis. Since associated foot injury is common, we compared the outcome for 12 cases of isolated subtalar luxation with 10 cases of collateral fractures of the adjacent bones of the hind foot and Talus. 19 cases of complex, partially open injuries after high energy trauma have got excluded becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Subtalar dislocations with associated fractures of the talus and the calcaneus are related to clear signs of osteoarthritis and poor clinical function, a finding that is consistent with previous research [20]. Those patients should be followed up shortly after the acute treatment and an early secondary arthrodesis should be discussed.…”
Section: Discussionsupporting
confidence: 76%
“…Subtalar dislocations with associated fractures of the talus and the calcaneus are related to clear signs of osteoarthritis and poor clinical function, a finding that is consistent with previous research [20]. Those patients should be followed up shortly after the acute treatment and an early secondary arthrodesis should be discussed.…”
Section: Discussionsupporting
confidence: 76%
“…Pure dislocations seem to have a more favorable prognosis compared to combined injuries and associated fractures [12,13]. In addition, open reduction and surgical fixation of the lesion was largely related to a poor result [14].…”
Section: Discussionmentioning
confidence: 99%
“…It also concluded that males were more commonly affected than females." [3][4][5][6][7] In this case report, we would like to present few cases of subtalar joint dislocation and their management that we encountered, in our clinical practice.…”
Section: Introductionmentioning
confidence: 99%